Original paperThe association between coronary slow flow and platelet distribution width among patients with stable angina pectoris - Ozyurtlu, Ferhat; Yavuz, Veysel; Cetin, Nurullah; Acet, Halit; Ayhan, Erkan; Isik, Turgay (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction: Coronary slow flow (CSF) is an angiographic phenomenon characterised by the delay of distal vessel opacification in the absence of significant stenosis of the epicardial coronary arteries. Some of the factors playing a role in CSF pathophysiology are increased thrombogenic activity and inflammation. Aim : To examine the relationship between platelet distribution width (PDW) and CSF. Material and methods : Taking into consideration the exclusion criteria, 136 patients with CSF and 152 patients with normal coronary angiographies (control group) were included in the study. The association between thrombolysis infarction frame count (TFC) in myocardial and laboratory and other clinical parameters were evaluated. Results: The stated parameters were significantly higher in the group with CSF than in the normal coronary angiography group (control group). The PDW (16.6 ±0.7 vs. 16.4 ±0.6, p = 0.002), neutrophil lymphocyte ratio (NLR) (3.1 ±3.4 vs. 2.4 ±1.1, p = 0.027), haemoglobin (Hb) (14.1 ±1.3 vs. 14.7 ±1.1, p 16.15 and Hb > 1 3.75 were predictors of the presence of CSF with sensitivities of 83% and 73% and specificities of 40% and 42%, respectively. Conclusions : This study has demonstrated that compared to normal coronary flow, PDW, Hb, NLR, and RDW are significantly higher in CSF patients. We believe that further studies are needed to clarify the role of PDW and Hb in patients with CSF.